Impact of cool and warm water immersion on 50-m sprint performance and lactate recovery in swimmers - Soultanakis, H. N.; Nafpaktiitou, D.; Mandaloufa, S. M. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this study was to investigate the impact of recovery by cool or warm water immersion, between two 50-m sprints on performance determinants and lactate responses in simulated competition conditions.